Вы находитесь на странице: 1из 1

Тригонометрические таблицы и уравнения

Release version 1.0


©RUffian 2006
x (deg) x (rad) sin x cos x tg x ctg x
0° 0 0 1 0 defunct
30° π/6 ½ √3/2 √3/3 √3
45° π/4 √2/2 √2/2 1 1
60° π/3 √3/2 ½ √3 √3/3
90° π/2 1 0 defunct 0
120° 2π/3 √3/2 –½ –√3 –√3/3
135° 3π/4 √2/2 –√2/2 –1 –1
150° 5π/6 ½ –√3/2 –√3/3 –√3
180° π 0 –1 0 defunct
210°= –150° –5π/6 –½ –√3/2 √3/3 √3
225°= –135° –3π/4 –√2/2 –√2/2 1 1
240°= –120° –2π/3 –√3/2 –½ √3 √3/3
270°= –90° –π/2 –1 0 defunct 0
300°= –60° –π/3 –√3/2 ½ –√3 –√3/3
315°= –45° –π/4 –√2/2 √2/2 –1 –1
330°= –30° –π/6 –½ √3/2 –√3/3 –√3
sin ( x ± y ) = sin x cos y ± cos x sin y ; cos 4x=2cos2 2x–1=8cos4 x–8cos2 x+1=1–2sin22x;
cos ( x ± y ) = cos x cos y sin x sin y ; sin x cos x = ½ sin 2x;
sin x sin y = ½ (cos (x – y) – cos (x + y));
tg x ± tg y
tg ( x ± y ) = ; sin x cos y = ½ (sin (x + y) + sin (x – y));
1 tg x tg y
cos x cos y = ½ (cos (x + y) + cos (x – y));
sin2 x + cos2 x = 1; x± y x y
sin4 x + cos4 x = ¼ cos 4x + ¾; sin x ± sin y = 2 sin cos ;
2 2
sin 2x = 2sin x cos x; x+ y x− y
cos 2x = cos2 x – sin2 x = 2cos2 x – 1 = 1 – 2sin2 x cos x − cos y = −2 sin sin ;
2 2
2tg 2x 3tg x − tg 3 x x+ y x− y
tg x = ; tg 3 x = ; cos x + cos y = 2 cos cos ;
1 − tg 2 2x 1 − 3tg 2 x 2 2
4tg x − 4tg 3 x 2tg 2x 1 − tg 2 2x
tg 4 x = ; sin x = 2 x ; cos x = ;
1 − 6tg 2 x + tg 4 x 1 + tg 2 1 + tg 2 2x
1 + tg2 x = 1 / cos2 x; sin 3x = 3sin x – 4sin3 x;
1 + ctg2 x = 1 / sin2 x; cos 3x = 4cos3 x – 3cos x ;
sin x + cos x = √2 sin (x + π/4); sin 3x – cos 3x = 3sin x–4sin3 x–4cos3 x + 3cos x;
sin x – cos x = √2 sin (x – π/4);
sin 4x = 8sin x cos3 x – 4sin x cos x = sin 3x cos x +
sin2 x = ½ (1 – cos 2x);
cos 3x sin x;
cos2 x = ½ (1 + cos 2x) = 1 / (tg2 x + 1);
sin3 x = ¼ (3sin x – sin 3x); sin x = 1; x = π/2 + 2πn;
cos3 x = ¼ (cos 3x + 3cos x); sin x = 0; x = πn;
sin4 x = 1/8 (cos 4x – 4cos 2x +3); sin x = –1; x = –π/2 + 2πn;
sin ( x ± y ) cos x = 1; x = 2πn;
tg x ± tg y = ;
cos x cos y cos x = 0; x = π/2 + πn;
sin x + cos x = 1 → sin x = 2sin a cos a; cos x = cos x = –1; x = π + 2πn;
cos2 a – sin2 a; 1 = sin2 a + cos2 a, где a = x/2